(3QSGdI GdJdHjI hGdJCfjH hGdJhHjN hGdJhajbs - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj , J (B433 (3g`s
(3ChdgG (B:s
(3ChUdJ Edi eYO Hf eMeO hGdi ef eYg HGdbGgQI ef GdebUQjf ai GdSfI GdQGHYI YTQ ef Sfjf bGFe GdReGf bhHdJ hUMJ s
(3BNQgG (B:s
(3hGdLhGH HeG aYdJ hGddg jhab ef SYi ai eQVGJg hjLRd KhGH GdTGcQjf hGdMeO dehdGfG hMOg hGdTcQ ddEeGe GdgGOi YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B42s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds